A FIRST REPORT OF A GERMLINE FRAMESHIFT C.332DUP MUTATION IN MEN1 GENE IN A PATIENT WITH MULTIPLE ENDOCRINE NEOPLASIA TYPE 1 - Plasheski, Tosho; Bitoska, Iskra; Jovanovska Mishevska, Sasha; Todorova, Biljana; Georgiev, Antonio; Mileva Kostovska, Ivana; Plaseska-Karanfilska, Dijana (MIT University Skopje, 2022)
Multiple endocrine neoplasia type 1 (MEN 1) is an autosomal dominant disease characterized by the appearance of endocrine tumors, most commonly parathyroid adenomas, gastro-entero-pancreatic endocrine tumors, and pituitary tumors. It is caused by inactivating mutations in the MEN 1 tumor suppressor gene. More than 1,300 mutations in the MEN1 gene have been described, most of which are family specific. In this paper we report a patient with MEN 1 syndrome with a c.332dup mutation in the MEN1 gene in a heterozygous form. The identification of MEN1 mutations allows the application of a specific diagnostic approach to the detection of MEN 1 associated tumors and lesions, dictates the timing of surgical procedures, and allows specific genetic analyzes of relatives to be performed to identify presymptomatic carriers.
ПРВО СООПШТЕНИЕ ЗА ГЕРМИНАТИВНА FRAME SHIFT C.332DUP МУТАЦИЈА ВО MEN1 ГЕНОТ КАЈ ПАЦИЕНТ СО МУЛТИПНА ЕНДОКРИНА НЕОПЛАЗИЈА ТИП 1
Keywords: c.332dup mutation in MEN1 gene; multiple endocrine neoplasia type 1